2014
DOI: 10.1016/j.febslet.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Expression of type I collagen and tenascin C is regulated by actin polymerization through MRTF in dedifferentiated chondrocytes

Abstract: a b s t r a c tThis study examined actin regulation of fibroblast matrix genes in dedifferentiated chondrocytes. We demonstrated that dedifferentiated chondrocytes exhibit increased actin polymerization, nuclear localization of myocardin related transcription factor (MRTF), increased type I collagen (col1) and tenascin C (Tnc) gene expression, and decreased Sox9 gene expression. Induction of actin depolymerization by latrunculin treatment or cell rounding, reduced MRTF nuclear localization, repressed col1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 34 publications
2
78
0
Order By: Relevance
“…Furthermore, loss of CDH11 either in Cdh11 −/− mouse dermal fibroblasts or in shCDH11 human dermal fibroblasts abolished the expression of transcription factors known to affect ECM synthesis (Ueyama et al, 2003;Medjkane et al, 2009;Small et al, 2010;Leitner et al, 2011;Velasquez et al, 2013;Johnson et al, 2014;Parreno et al, 2014), such as MYOCD, MRTF-A, SRF and to a lesser extent MRTF-B. In agreement, knocking down either MYOCD or MRTF-A and -B decreased CDH11-mediated expression of collagen and elastin, but the effects of MRTF-A and -B were significantly stronger.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, loss of CDH11 either in Cdh11 −/− mouse dermal fibroblasts or in shCDH11 human dermal fibroblasts abolished the expression of transcription factors known to affect ECM synthesis (Ueyama et al, 2003;Medjkane et al, 2009;Small et al, 2010;Leitner et al, 2011;Velasquez et al, 2013;Johnson et al, 2014;Parreno et al, 2014), such as MYOCD, MRTF-A, SRF and to a lesser extent MRTF-B. In agreement, knocking down either MYOCD or MRTF-A and -B decreased CDH11-mediated expression of collagen and elastin, but the effects of MRTF-A and -B were significantly stronger.…”
Section: Discussionmentioning
confidence: 57%
“…2a; right panel and 2B). To further confirm these changes in the actin cytoskeleton, we quantified levels of F- and G-actin using selective solubilisation of G-actin in Triton-X-100, as previously described 37 . This demonstrated that forskolin stimulation of VSMC resulted in a significant reduction in F-actin and a significant increase in G-actin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…F- and G-actin were separated by triton solubility essentially as previously 37 described with slight modifications. Following treatment, G-actin was extracted in G-actin extraction buffer (PBS, 10% glycerol, 0.1% triton X-100, 1 mM ATP and complete protease inhibitor) and incubated for 5 min at room temperature with slight agitation.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogels are particularly convenient since they induce cell rounding and round morphology associated with depolymerized actin is essential for correct chondrogenic expression . On the contrary, in a 2D environment such as a phase of cellular expansion on plastic, chondrocytes adopt a fibroblastic shape associated with polymerized actin and this results in chondrocyte dedifferentiation . In this study, we hypothesized that an SAP IEIK13 hydrogel would provide an appropriate 3D environment for encapsulation of chondrocytes.…”
Section: Discussionmentioning
confidence: 99%